A Critical Evaluation of the Four-Year B. Sc. Mathematics Curriculum at Tribhuvan University - Kumar, Nanda Kishor (Curriculum Development Journal, 2023)
A synopsis of the existing four-year B.Sc. mathematics curriculum offered by the Institute of Science and Technology is given. The main structure, the course’s advantages and disadvantages, and some suggestions are provided. It is necessary to make improvements in the existing curriculum to maintain T.U.’s academic standards at the highest level worldwide. The objective of the four-year B.Sc. program still needs a lot of tweaking and adjusting. The author of mathematics textbooks should consider the aims and objectives of the subject matter taught in that class.